Pesticide risk indicator for terrestrial adult stages of aquatic insects. (November 2020) - Sørensen, Peter Borgen; Kjær, Christian; Wiberg-Larsen, Peter; Bruus, Marianne; Strandberg, Beate; Rasmussen, Jes Jessen; Damgaard, Christian F.; Larsen, Søren E.; Strandberg, Morten
Highlights: A new pesticide indicator is suggested. The target is freshwater insects during the reproductive terrestrial life stage. Temporal and spatial distribution of abundance and deposition are combined. Abstract: Many taxonomic groups of freshwater insects have a reproductive terrestrial life stage, and some are highly sensitive to insecticides. In agricultural landscapes, it is likely that streams and rivers often run along agricultural fields treated with pesticides, but the risk to insects with a reproductive terrestrial life stage due to pesticide exposure is not well-covered by existing risk indicators. Different aquatic insect species may have different strategies for feeding and mating and, thus, different spatial and temporal distribution of the terrestrial abundance. This influences the fraction of individuals that can suffer from pesticide exposure, and thus the risk indicator in this paper includes spatial and temporal distributions of both insect abundance and air born pesticide deposition, in this case multiplied together and weighted with toxicity. The indicator is denoted Adult Stage Risk Indicator, ASRIi, j, and can be calculated for every combination of insect taxon i, and pesticide active ingredient j . An Excel/VBA based model is available as Supplementary material . However, setting up the indicator using another platform is simple, and for any application please refer to this paper.